Impact of local rivers on coastal acidification. Issue 12 (10th October 2022) - Savoie, Allison M.; Moody, Amy; Gilbert, Melissa; Dillon, Kevin S.; Howden, Stephan D.; Shiller, Alan M.; Hayes, Christopher T.
Abstract: Coastal ecosystems are highly dynamic areas for carbon cycling and are likely to be negatively impacted by increasing ocean acidification. This research focused on dissolved inorganic carbon (DIC) and total alkalinity (TA) in the Mississippi Sound to understand the influence of local rivers on coastal acidification. This area receives large fluxes of freshwater from local rivers, in addition to episodic inputs from the Mississippi River through a human‐built diversion, the Bonnet Carré Spillway. Sites in the Sound were sampled monthly from August 2018 to November 2019 and weekly from June to August 2019 in response to an extended spillway opening. Prior to the 2019 spillway opening, the contribution of the local, lower alkalinity rivers to the Sound may have left the study area more susceptible to coastal acidification during winter months, with aragonite saturation states (Ωar ) < 2. After the spillway opened, despite a large increase in TA throughout the Sound, aragonite saturation states remained low, likely due to hypoxia and increased CO2 concentrations in subsurface waters. Increased Mississippi River input could represent a new normal in the Sound's hydrography during spring and summer months. The spillway has been utilized more frequently over the last two decades due to increasing precipitation in the Mississippi River watershed, which is primarily associated with climate change. Future increases in freshwater discharge and the associated declines in salinity, dissolved oxygen, and Ωar in the Sound will likely be detrimental to oyster stocks and the resilience of similar ecosystems to coastal acidification.